Onychomycosis : An Illustrated Guide to Diagnosis and Treatment - Tosti, Antonella; Vlahovic, Tracey C.; Arenas, Roberto (Springer International Publishing : Imprint: Springer, 2017)
There are an estimated 32 million people with onychomycosis in the United States alone, making it the most common nail disease seen and treated, but also quite misunderstood. With the sole focus of this book devoted to onychomycosis, the reader is provided with insight into the diagnosis and management of this nail infection. Onychomycosis includes chapters on how fungus infects the nail unit, the types of nail fungus, diagnosis from a gross and microscopic view, and the various treatment options available. With chapters written by the world's experts along with dozens of high quality color photographs and illustrations, this book is a practical reference guide for every dermatologist, podiatrist, and primary care physician.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books